The 4th Michigan Infantry in the Civil War - Bertera, Martin N. (Michigan State University Press, 2010)
From the Publisher: This fascinating narrative tells the story of a remarkable regiment at the center of Civil War history. The real-life adventure emerges from accounts of scores of soldiers who served in the 4th Michigan Infantry, gleaned from their diaries, letters, and memoirs; the reports of their officers and commanders; the stories by journalists who covered them; and the recollections of the Confederates who fought against them. The book includes tales of life in camp, portraying the Michigan soldiers as everyday people-recounting their practical jokes, illnesses, political views, personality conflicts, comradeship, and courage. The book also tells the true story of what happened to Colonel Harrison Jeffords and the 4th Michigan when the regiment marched into John Rose's wheat field on a sweltering early July evening at Gettysburg. Beyond the myths and romanticized newspaper stories, this account presents the historical evidence of Jeffords's heroic, yet tragic, hand-to-hand struggle for his regiment's U.S. flag. After men from the regiment witness the surrender of Gen. Robert E. Lee at Appomattox Court House, they expect to return home. But as the book reveals, to their dismay they are kept in service and assigned to Texas for a one-year stint that seems interminable.